Identification of two new GRAS transcription factors and expression analysis of these genes in Chenopodium quinoa - Hou, Xinwen; Wang, Shuwei; Zhou, Shanmin; Liu, Weizhong (Frontiers in Plant Science, 2025)
Chenopodium quinoa is a relatively new and excellent crop, and its growth is frequently threatened by abiotic stress. GRAS genes are considered to be a plant-specific transcriptional regulatory family, which is essential for controlling aboveground and root development, as well as enhancing tolerance to abiotic stress. Phylogeny, gene structure, genomic location, conserved motif, cis-element, protein interaction, and expression pattern were all comprehensively investigated in this research of the quinoa GRAS genes. According to its structure and phylogenetic characteristics, the identified quinoa 54 GRAS members were divided into 10 subgroups. The distribution of CqGRAS genes on 19 quinoa chromosomes is uneven, with Chr07 and Chr18 having the largest number of genes. The quinoa GRAS family’s evolution has been driven by duplication and collinearity among members. Under abiotic stress, 12 selected CqGRAS genes showed significant differential expression. CqGRAS1 and 19 were most sensitive to low temperatures, H2O2 treatment highly induced the expression of CqGASS20, and Na2CO3 treatment highly induced the expression of CqGRAS23. After conducting tissue quantification, we found that some CqGRAS genes exhibit tissue-specific expression patterns, with CqGRAS19 and 45 being highly expressed in stems and CqGRAS3 and 32 being highly expressed in leaves. In summary, this work gives valuable information for a comprehensive understanding of the functional analysis of the Chenopodium quinoa genome’s GRAS gene family and the identification of candidate genes to improve quinoa’s resistance to abiotic stress.